Phylogenetic and Morphological Evolution of Green Euglenophytes Based on 18S rRNA. (27th December 2020) - Wang, Yanmei; Feng, Jia; Lv, Junping; Liu, Qi; Nan, Fangru; Liu, Xudong; Xie, Shulian
Abstract: Green euglenophytes are a group of eukaryotes with ancient origin. In order to understand the evolution of the group, it is interesting to know which characteristics are more primitive. Here, a phylogenetic tree of green euglenophytes based on the 18S rRNA gene was constructed, and ancestral states were reconstructed based on eight morphological characters. This research clarifies the phylogenetic relationships of green euglenophytes and provides a basis for the study of the origin of these plants. The phylogenetic tree, which was constructed by Bayesian inference, revealed that: Eutreptia and Eutreptiella were sister groups and that Lepocinclis, Phacus, and Discoplastis were close relatives; Euglena, Cryptoglena, Monomorphina, and Colacium were closely related in addition to Trachelomonas and Strombomonas ; and Euglena was not monophyletic. An ancestral reconstruction based on morphological characters revealed seven primitive character states: ductile surface, spirally striated, slightly narrowing or sharp elongated cauda, absence of a lorica, chloroplast lamellar, shield or large discoid, pyrenoid with sheath, and with many small paramylon grains. However, the ancestral state of the length of the flagellum could not be inferred. Euglena and Euglenaria, which both possessed all of the ancestral character states, might represent the most ancient lineages of green euglenophytes.